An evaluation of symptom and chest radiographic screening in tuberculosis prevalence surveys - den Boon, S; White, N W; van Lill, S W P; Borgdorff, M W; Verver, S; Lombard, C J; Bateman, E D; Irusen, E; Enarson, D A; Beyers, N (The international journal of tuberculosis and lung disease, 2006)
A tuberculosis (TB) prevalence survey was performed in 2002 in two urban communities in Cape Town, South Africa. The population was 36,334 in 2001, and the TB notification rate was 341 per 100,000 population for new smear-positive TB in 2002. To evaluate the relative contributions of symptom and chest radiographic (CXR) screening in the detection of subjects with smear- and/or culture-positive TB in prevalence surveys. Information on symptoms, CXR abnormalities, sputum smear and culture was gathered from a random cluster sample of 1170 adults (aged > or = 15 years). Smear and/or culture-positive TB was used as the gold standard. Of 1170 adults, 29 had bacteriologically positive TB (smear- and/or culture-positive). The presence of any abnormalities on CXR had the highest sensitivity for detecting subjects with bacteriologically positive TB (0.97, 95%CI 0.90-1.00). Specificity for any abnormalities on CXR was 0.67 (95%CI 0.64-0.70). The specificity of any of five TB-related symptoms was 0.68 (95%CI 0.65-0.71). Individual symptoms had low sensitivities, ranging from 0.10 for fever to 0.54 for cough of > or = 2 weeks. In this TB prevalence survey, CXR screening, but not symptom screening, was a sensitive alternative to sputum examination of all participants.